(untitled) (Ustozlar uchun, 2026)
This article examines linguistic, strategic, and sociolinguistic competences as fundamental components of communicative competence in language learning. The study analyzes their theoretical foundations and functional roles in effective communication. Linguistic competence refers to knowledge of grammar, vocabulary, phonology, and syntactic structures necessary for producing accurate language. Sociolinguistic competence involves the ability to use language appropriately according to social context, cultural norms, and interpersonal relationships. Strategic competence enables learners to overcome communication difficulties, repair breakdowns, and maintain interaction through compensatory strategies. The article highlights the interrelationship among these competences and emphasizes their integrated development in foreign language teaching. The findings suggest that successful communication depends on the balanced interaction of structural knowledge, social awareness, and communicative strategies.